2006
DOI: 10.1021/jf0620719
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Antioxidant and Antiinflammatory Effects of Flavonols

Abstract: The antioxidant and antiinflammatory effects of flavonols have been suggested to be structure-related. Results revealed that selected flavonols, including fisetin (F), kaempferol (K), morin (MO), myricetin (MY), and quercetin (Q), exhibited distinctive free radical scavenging properties against different kinds of free radicals. The H donation (DPPH bleaching) potential was Q > F approximately equals MY > MO > K, indicating that the presence of a 3',4'-catechol moiety in the B ring correlated with high activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
203
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(221 citation statements)
references
References 32 publications
13
203
0
5
Order By: Relevance
“…The same dose of fisetin also reduced LPS-induced increases in extracellular PGE2 levels as well as increases in the expression of the COX2, iNOS and interleukin-1b genes. Similar to the results obtained with other types of cells treated with fisetin and LPS [85,92], the effects of fisetin on microglial activation appeared to be mediated by inhibition of LPS-stimulated NF-jB activation. Similar data were obtained with primary microglial cells isolated from the cerebral cortices of 1 day old mice.…”
Section: Anti-inflammatory Effects Of Fisetinsupporting
confidence: 85%
“…The same dose of fisetin also reduced LPS-induced increases in extracellular PGE2 levels as well as increases in the expression of the COX2, iNOS and interleukin-1b genes. Similar to the results obtained with other types of cells treated with fisetin and LPS [85,92], the effects of fisetin on microglial activation appeared to be mediated by inhibition of LPS-stimulated NF-jB activation. Similar data were obtained with primary microglial cells isolated from the cerebral cortices of 1 day old mice.…”
Section: Anti-inflammatory Effects Of Fisetinsupporting
confidence: 85%
“…Four compounds (genistein, kaempferol, quercetin, and daidzein) inhibited the activation of two important gene transcription factors for iNOS, i.e., signal transducer and activator of transcription 1 (STAT-1) and NF-kB, whereas four other compounds (flavone, isorhamnetin, naringenin, and pelargonidin) only inhibited NF-kB (Hämälänein et al, 2007). Another study showed that selected flavonoids, including fisetin, kaempferol, morin, myricetin, and quercetin, exhibited distinct antioxidant properties against different types of free radicals (Wang et al, 2006). These results indicate that flavonoids have different antioxidant and anti-inflammatory effects despite their structural similarity (Hämälänein et al, 2007;Wang et al, 2006).…”
Section: Anti-inflammatory and Immunomodulatory Response To Isolated mentioning
confidence: 99%
“…Another study showed that selected flavonoids, including fisetin, kaempferol, morin, myricetin, and quercetin, exhibited distinct antioxidant properties against different types of free radicals (Wang et al, 2006). These results indicate that flavonoids have different antioxidant and anti-inflammatory effects despite their structural similarity (Hämälänein et al, 2007;Wang et al, 2006). Some flavonoids stimulate macrophages stop further production of eicosanoids and destroy excess oxidants (Havsteen, 2002).…”
Section: Anti-inflammatory and Immunomodulatory Response To Isolated mentioning
confidence: 99%
“…Flavonoids have long been recognized to exhibit antiinflammatory, antioxidant, anti-allergic, hepatoprotective, antithrombotic, anti-viral, anti-carcinogenic activities and immune modulating functions, among others [8][9][10][11]. The flavonoids also act as potent metal chelators and free radical scavengers and are powerful chain-breaking antioxidants [12], and control protein oxidation and advanced glycation end products (AGEs) formation [13].…”
Section: Introductionmentioning
confidence: 99%
“…The position and the degree of hydroxylation have been demonstrated to be the most important for their biochemical and pharmacological actions [25,26]. Wang et al [11] examined the antioxidant and antiinflammatory activities of selected flavonols, including kaempferol, quercetin and myricetin. Their results showed that flavonols exhibit distinctive antioxidant and anti-inflammatory potentials and that the structures, required to strengthen these activities, vary with sorts of free radicals and mechanisms.…”
Section: Introductionmentioning
confidence: 99%